The Impact and Challenges of South African School Feeding Programmes in the COVID-19 Context - Eridiong Onyenweaku; Hema Kesa (Shiraz University of Medical Sciences, 2023)
Background: Many individuals are grappling with food insecurity due to the ongoing global recession. Childhood malnutrition poses a risk factor for adult morbidities, underscoring the need for cost-effective strategies to prevent and combat this issue. This study aimed to determine the impact and challenges of in-school nutrition programs, shedding light on the difficulties faced within the context of the COVID-19 pandemic.Methods: A cross-sectional survey of schools across four South African provinces-Gauteng, Western Cape, Northwest, and KwaZulu-Natal-was conducted between April 2022 and May 2022. A total of 36 schools were selected at random. Three interviews (questionnaires) were administered to each school's principal, teacher, and food handler. Additionally, an observational checklist was employed. Qualitative data underwent thematic analysis utilizing an inductive approach through Atlas. ti software, while Microsoft Excel was utilized to analyze the checklist data. Results were presented using descriptive statistics.Results: The school communities have experienced substantial overall benefits from the school feeding programs. Survey results demonstrated a noteworthy reduction in the prevalence of unemployment, poverty, dependency on grants, and larger families within the surveyed districts. However, some meals were consumed less frequently due to a lack of flavor.Conclusions: The school feeding programs have yielded positive impacts. In order to enhance outcomes, there is a need to incorporate more protein-rich foods (such as meat and eggs) and a more comprehensive array of spices/flavors. These changes will respectively enhance the nutritional content and appeal of the meals.